EVALUASI PENGARUH BAHAYA GEMPA RENCANA TERHADAP POTENSI TIMBULNYA KORBAN JIWA PADA BANGUNAN PEMERINTAH DI KABUPATEN INDRAGIRI HILIR MENGGUNAKAN METODA FEMA P-58-5 - Rofriantona Rofriantona; Ridwan Ridwan; Zulfikar Djauhari (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2023)
The FEMA P-58-5 method is a method used to obtain the performance of a building structure using a probability approach. The purpose of this reserach is to obtain the performance of the object prior to pinfluence of the planned earthquake (2017 Earthquake Hazard Map).The object is a government building in Tembilahan City, consists of : Immigration Office, Regent's Office, Puri Husada Hospital and Rusunawa. Geographically, Tembilahan is located at coordinates 103° 9' 28" E, 0° 18' 54" S. Base on the provisions of SNI 1726-2019, the soil characteristics of the city of Tembilahan is belongs to soft soil site class (SE). The FEMA P-58-5 method uses the PACT program. The first step is to determine the seismic hazard level, type of the main lateral load-bearing structure, the function of the building, risk category, number of floors, base shear force and story drift . The second step is to input the variable data into PACT. The third step is to analyze the FEMA P-58 PACT output, collapse probability, casualty rate, mean repair time, total repairability, unsafe placardThe results of building structure is categorized as safe, assessed from the collapse fragility variable, 0.4%. Damage that occurs is assessed from structural components that can be repaired (total repairability variable) is ± 92.83% and the potential for fatalities (casualty rate variable), ± 0.4%). The correlation of the variables using the FEMA P-58-5 method concluded that the collapse fragility variable is directly proportional to the variables of unrepairable permanent drift, median loss probability, mean loss probability, casualty rate, total repairability, mean repair time and unsafe placard. Evaluation of building performance using the FEMA P-58-5 method estimates that the structure of the building suffered light to severe damage (sequential): Puri Husada Hospital Tembilahan, Immigration Office, Regent's Office and Rusunawa Tembilahan. Potensial of casualty rate for government building users respectively are RSUD Puri Husada Tembilahan (0,1 %), Kantor Imigrasi (1,1 %), Kantor Bupati (0,2 %) dan Rusunawa Tembilahan (0,2 %)